2018
DOI: 10.1002/macp.201800059
|View full text |Cite
|
Sign up to set email alerts
|

Endo/Exo Reactivity Ratios in Living Vinyl Addition Polymerization of Substituted Norbornenes

Abstract: Substituted norbornenes may be enchained by vinyl addition polymerization (VAP), through the norbornene double bond. Such monomers are generally prepared by Diels–Alder cycloaddition of cyclopentadiene and the corresponding olefin, which leads to a mixture of endo and exo stereoisomers with potentially very different reactivity, but these differences have not previously been quantified (e.g., as copolymerization reactivity ratios rendo and rexo). A living Pd‐based VAP initiator is employed and the consumption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 43 publications
0
31
0
1
Order By: Relevance
“…This mixture is, as a rule, enriched by an endo-isomer that is less reactive in polymerizations. 16,17 To overcome this disadvantage, the [2s + 2s + 2p]-cycloaddition of vinylsilanes with quadricyclane was realized (Scheme 1b). 18 This selectively gives the exo-isomer, but only "activated" vinylsilanes (which contain chlorine atoms at silicon) were active in this reaction.…”
Section: Introductionmentioning
confidence: 99%
“…This mixture is, as a rule, enriched by an endo-isomer that is less reactive in polymerizations. 16,17 To overcome this disadvantage, the [2s + 2s + 2p]-cycloaddition of vinylsilanes with quadricyclane was realized (Scheme 1b). 18 This selectively gives the exo-isomer, but only "activated" vinylsilanes (which contain chlorine atoms at silicon) were active in this reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Both norbornene derivatives exhibited high polymerization reactivities, and the corresponding polymers were obtained in good yields with high molecular weights (Table ). The syntheses of various addition homo‐ and copolymers from 5‐alkyl‐2‐norbornenes have been described in the literature; however, to the best of our knowledge, addition poly(5‐ n ‐octyl‐2‐norbornene) is a new polymer. The structure of the polymers was confirmed with the help of NMR‐ and IR‐spectroscopy (Figures S1 and S2, Supporting Information).…”
Section: Methodsmentioning
confidence: 69%
“…The second reason is the used DCPD was enriched by a less reactive endo ‐isomer, while HexNB consisted of approximately equal amounts of exo ‐ and endo ‐isomers. Thus it was shown that in addition polymerization of norbornenes, exo ‐derivatives as a rule are more reactive than endo ‐isomers . The last reason is the capability of DCPD to form stable chelates with the catalyst active species ( Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus it was shown that in addition polymerization of norbornenes, exo-derivatives as a rule are more reactive than endo-isomers. [44,45] The last reason is the capability of DCPD to form stable chelates with the catalyst active species (Figure 7). Thus, the presence of the second double bond in DCPD leads to the possibility to coordinate with Pd-centers in different ways (Figure 7, structures I-III) and there is a competition between these double bonds for the vacant coordination place at Pd-complexes.…”
Section: Addition Copolymerization Of Dicyclopentadiene and 5-n-hexylmentioning
confidence: 99%